Rectovaginal Examination, Transvaginal Ultrasonography, and Magnetic Resonance Imaging as Diagnostic Tools for Identifying Deep Infiltrating Endometriosis Nodules: Rectovaginal Toucher, Ultrasonografi Transvaginal dan Magnetic Resonance Imaging sebagai Modalitas Penunjang Diagnosa Nodul Endometriosis Susukan Dalam - Florencia Wirawan; Luky S Marwali; Refni Muslim; Eva R Silalahi; Harjo S Bayuaji; Astri Anindita (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: To investigate the comparison between rectovaginal examination (RVT), transvaginal ultrasonography (TVUS) and magnetic resonance imaging (MRI) as diagnostic tools for identifying various Deep Infiltrating Endometriosis (DIE). Methods: Prospective longitudinal study was done involving 31 women referred for surgical management of DIE. Calculation of sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of RVT, TVUS and MRI for DIE were recorded. Results: The mean age was 35.1 years. DIE were present in 95.45% of women which commonly located at uterosacral ligaments (58.33%), followed by rectovaginal (16,67%), rectosigmoid- colon (16.67%) and bladder-ureter (8.3%). TVUS had the best accuracy (RVT 50.24%; TVUS 88.85%; MRI 75.77%) among other diagnostic tools for nodules located at uterosacral ligaments (RVT 52.63%; TVUS 87%; MRI 40%) and rectovaginal (RVT 76.75%; TVUS 93.34%; MRI 80%), but it poorly identified nodules located at rectosigmoid (RVT 20%; TVUS 65.56%; MRI 88.75%) and bladder-ureteral area (RVT 50.44%; TVUS 87.66%; MRI 93.55%). RVT had good PPV (88.89%) but bad NPV (32.01%) profile, made it worth to be a screening diagnostic tool. Conclusion: RVT was a good screening diagnostic tools as it could be done easily but was weak in diagnosing anterior DIE. TVUS gave a better diagnosis rates on DIE located at sacrouterina ligaments and rectovaginal area whereas MRI did better on bowel DIE (rectosigmoid- colon area) and urological DIE (bladder-ureteral area). Keywords: deep infiltrating endometriosis, magnetic resonance imaging, tranvaginal ultrasonography